Plasma Polymerization of Styrene Using an Argon-Fed Atmospheric Pressure Plasma Jet - Tan, Paolo Edward C (Archīum Ateneo, 2018)
In this paper, the authors describe an alternative polymerization process of styrene monomer. Styrene, placed in a Plexiglas crucible to minimize splattering, was treated with an argon-atmospheric plasma jet, at a gas flow rate of 12.5 standard cubic feet per hour for 12 min, using a 450-W neon sign transformer power supply. Treated samples were transferred from the crucible to glass substrates and allowed to dry at room temperature. Solvent washing analysis showed an average product retention of 66.59% proving that polymerization occurred. Contact angle measurements of the treated samples showed an increase in hydrophobicity from 78.12° for untreated styrene to 88.14° for plasma-treated styrene. Fourier transform infrared analysis revealed the absence of the C=C, C=C-H and the presence of the C=O and C-O-C functional groups upon treatment. It was concluded that styrene was polymerized successfully through the use of an argon fed atmospheric pressure plasma jet, and that hydrophobic plasma-polymerized polystyrene coatings were successfully deposited onto glass substrates.